(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
Adolescence is characterized by fast pubertal changes and high nutrient needs which are often unmet due to household food insecurity. The prevalence of household food insecurity among in-school adolescents in a peri-urban settlement in Nigeria and its impact on micronutrient deficiencies was determined. Household Food Insecurity Access Scale (HFIAS) questionnaire was used to assess household food insecurity. Zinc, iron, vitamin A, and calcium concentrations were determined. Results were analysed using the EXCEL spreadsheet and presented as percentages and frequencies except where otherwise stated. The study revealed that most in-school adolescents are predominantly males (57.52%) of 16.18±1.75 average age and from households with limited social and economic resources. Eighty-seven percent of the adolescents from households with moderate (76.99%) to large (13.27%) sizes and monthly income below 75 have both the head of household and caregiver with limited educational attainment. Boreholes were the primary drinking water source (66.37%) for the households. About 83.3% of the households experience varied degrees of food insecurity while <30% of adolescents met their recommended dietary diversity. The anthropometric indices, BMI-for-age and Height-for-age z-scores revealed high prevalence of thinness (61.06%) and stunting (57.52%). The mean iron level was significantly (p=0.042) lower than the normal range. The frequency distribution shows iron (95.3%), zinc (54.7%), calcium (33.3%) and vitamin A (40.0%) deficiencies in the adolescents. Our results suggest that large household sizes result in adolescent food insecurity, below normal micronutrient levels, and dietary diversity in the study area, a peri-urban settlement in Northwest, Nigeria.